Strategies to enhance linkages between care for HIV/AIDS in jail and community settings. - Draine, Jeffrey; Ahuja, Divya; Altice, Frederick L; Arriola, Kimberly Jacob; Avery, Ann K; Beckwith, Curt G; Booker, Cristina A; Ferguson, Ann; Figueroa, Hayley; Lincoln, Thomas; Ouellet, Lawrence J; Porterfield, Jeffrey; et al. (AIDS care, 2011)
The policies of mass incarceration and the expansion of the criminal justice system in the USA over the last 40 years have weighed heavily on individuals and communities impacted by drug use and HIV disease. Though less than ideal, jails provide a unique opportunity to diagnose, treat and implement effective interventions. The role of jails in HIV detection, treatment, and continuity of care, however, has yet to be systematically examined. This paper reviews the service strategies and contexts for 10 demonstration sites funded to develop innovative methods for providing care and treatment to HIV-infected individuals in jail settings who are returning to their communities. The sites have implemented varied intervention strategies; each set in unique policy and service system contexts. Collaboration among agencies and between systems to implement these interventions is viewed as particularly challenging undertakings. We anticipate the sites will collectively serve 700-1000 individuals across the duration of the initiative. In this paper, we review the service contexts and strategies developed by the 10 sites. The individual and multi-site evaluations aim to provide new data on testing, treatment, and community linkages from jails that will further develop our knowledge base on effective intervention strategies in these settings.
Keywords: Case Management; Community Health Services; Continuity of Patient Care; Delivery of Health Care; Female; HIV Infections; HIV Seropositivity; Humans; Male; Policy Making; Prisoners; Prisons